Effect of ‘Galamsey’ on Human Fertility: A Systematic Review - Samuel Kofi Arhin; Precious Barnes; Isaiah Kofi Arhin; Benedicta Owusu‐Nyarko (Health Science Reports)
ABSTRACT Background and Aims In Ghana, the term ‘galamsey’ refers to illicit small‐scale gold mining. It is a primary factor in water pollution, land degradation and other environmental harm. It has also been connected to health risks like displacement and mercury poisoning. The rates of infertility among humans are rising, according to a recent study. While there are several theories explaining the rise in infertility rates, environmental contaminants may be a significant contributing role in this phenomenon. Fertility in both men and women can be impacted by a variety of environmental factors. The possible impacts of environmental contaminants on reproduction are especially concerning. We systematically reviewed the published literature on the effects of chemicals used in ‘galamsey’ on reproductive function. Methods A comprehensive search of major databases including Medical and Allied Healthcare databases was systematically searched to identify studies published within the last period of 2010–2022. The modern SPIDER template for eligibility criteria was adopted as a guide in study selection after a literature search. Two reviewers independently screened studies for eligibility, extracted data, and assessed study quality. Results Out of the 500 database, 20 documents were processed for their eligibility while 15 were included in the current study. The findings revealed that there is an association between the use of metals and reduced fertility in both males and females. ‘Galamsey’ exposure was also linked to decreased sperm count, motility and morphology in males as well as hormonal imbalance and increased chances of miscarriage and still birth among conceived mothers and females. Children born in these areas may have various forms of defects and malformations. Conclusion This systematic review provides evidence that illegal mining activities have a deleterious effect on human fertility. These findings highlight the need for environmental and health reforms to address future public health threats.